Stephen P. Long: Visionary, teacher, and doer - Elizabeth A. Ainsworth; Donald R. Ort (Proceedings of the National Academy of Sciences, 2026)
Stephen Long pioneered a multidisciplinary approach to advance our knowledge of photosynthesis, by integrating research at the molecular, cellular, organismal, and ecological levels along with a pragmatic understanding of the implications for agriculture. This involved development of new mathematical models, patented equipment for analyzing photosynthetic efficiency, and the world’s largest open-air laboratory for understanding crop responses to atmospheric change. Long fundamentally changed our understanding of how crops respond to rising CO 2 and ozone. He inspired and led efforts to engineer photosynthesis to increase yield and respond maximally to rising CO 2 . He discovered that C 4 plants, that have highly efficient photosynthesis due to a CO 2 concentrating mechanism, could thrive in cold climates, which was a true paradigm shift as previously C 4 photosynthesis had been considered limited to tropical and subtropical climates. He provided a theoretical explanation, and his research led to the discovery that Miscanthus x giganteus could achieve the high yields in cool northern climate achieved by other C 4 plants in the tropics. This seminal finding led Long to experiment on the closely related and much more widely used maize plant, and he showed how it could be adapted to cooler conditions and achieve a significant yield jump in the Corn Belt. At a time when society critically needed new ways to achieve increases in productivity in ecologically sustainable ways, Long’s research and leadership changed the way we think about choices of plants and cropping systems.